The Late Paleozoic relative gas fields of coal measure in China and their significances on the natural gas industry - Chenchen Fang; Jinxing Dai; Wei Wu; Dan Liu; Ziqi Feng (Journal of Natural Gas Geoscience, 2016)
The coal measure gas sources of coal-derived gas fields in the Late Paleozoic China are the Lower Carboniferous Dishuiquan Formation, the Upper Carboniferous Batamayineishan Formation and Benxi Formation, the Lower Permian Taiyuan Formation and Shanxi Formation, and the Upper Permian Longtan Formation. The coal-derived gas accumulates in Ordovician, Carboniferous, Permian, and Paleocene reservoirs and are distributed in Ordos Basin, Bohai Bay Basin, Junggar Basin, and Sichuan Basin. There are 16 gas fields and 12 of them are large gas fields such as the Sulige large gas field which is China's largest reserve with the highest annual output. According to component and alkane carbon isotope data of 99 gas samples, they are distinguished to be coal-derived gas from coal-derived gas with δ13C2 > −28.5‰ and δ13C1 -δ13C2 -δ13C3 identification chart. The Late Paleozoic relative gas fields of coal measure are significant for the Chinese natural gas industry: proven natural gas geological reserves and annual output of them account for 1/3 in China, and the gas source of three significant large gas fields is coal-derived, which of five significant large gas fields supporting China to be a great gas producing country. The average reserves of the gas fields and the large gas fields formed from the late Paleozoic coal measure are 5.3 and 1.7 times that of the gas fields and the large gas fields in China.